Effects of plasma-derived exosomes from the normal and thin Bactrian camels on hepatocellular carcinoma and their differences at transcriptome and proteomics levels - Yao, Hongqiang; Yu, Siriguleng; Luo, Yuchen; Wang, Ming; Wang, Xiuying; Xu, Siriguleng; Chen, Yufei; Xie, Zhifeng (Frontiers in Oncology, 2023)
Background: Hepatocellular carcinoma (HCC) is a common malignant primary tumor. Bactrian camels have high economic and social values, but their potential medical value has not been studied. This study aimed to investigate the effects of Bactrian camel plasma-derived exosomes on HCC. Methods: Plasma was obtained from thin and normal Bactrian camels, and used to isolate exosomes by ultracentrifugation. The exosomes were then characterized by transmission electron microscopy and Nano particle tracking analyzer. In vivo imaging of nude mice and hematoxylin eosin (HE) staining of liver tissues were used to explore the effects of the exosomes on tumor growth. Finally, the differences of the two exosomes were further analyzed using small RNA sequencing and proteomics. Results: In vivo imaging and HE staining showed that no significant differences were found in fluorescence value and liver tissue morphology between the control mice and the mice treated with the exosomes from thin Bactrian camels; while the fluorescence value and the live histology changes were alleviated in the mice with the exosomes from normal Bactrian camels. After sequencing and proteomic analysis, 40 DE-miRNAs (15 down-regulated and 25 up-regulated) and 172 DEPs (77 up-regulated and 95 down-regulated) were identified in the plasma-derived exosomes from normal Bactrian camels. These identified DE-miRNAs and DEPs were significantly enriched in many signaling pathways. Conclusions: Normal Bactrian camel plasma-derived exosomes may inhibit the growth of HCC cells through regulating pathways of Ras, Rap1, PI3K-Akt, MAPK, AMPK, and canonical Wnt signaling pathways.